"In Our Corner": A Qualitative Descriptive Study of Patient Engagement in a Community-Based Care Coordination Program. (March 2018) - Sefcik, Justine S.; Petrovsky, Darina; Streur, Megan; Toles, Mark; O'Connor, Melissa; Ulrich, Connie M.; Marcantonio, Sherry; Coburn, Ken; Naylor, Mary D.; Moriarty, Helene
The purpose of this study was to explore participants' experience in the Health Quality Partners (HQP) Care Coordination Program that contributed to their continued engagement. Older adults with multiple chronic conditions often have limited engagement in health care services and face fragmented health care delivery. This can lead to increased risk for disability, mortality, poor quality of life, and increased health care utilization. A qualitative descriptive design with two focus groups was conducted with a total of 20 older adults enrolled in HQP's Care Coordination Program. Conventional content analysis was the analytical technique. The overarching theme resulting from the analysis was "in our corner, " with subthemes "opportunities to learn and socialize" and "dedicated nurses, " suggesting that these are the primary contributing factors to engagement in HQP's Care Coordination Program. Study findings suggest that nurses play an integral role in patient engagement among older adults enrolled in a care coordination program.